Crouzon Syndrome with Bony Upper Airway Obstruction: Case Report and Review Literature. (1st August 2014) - Gothwal, Sunil; Nayan, Swati; Kumar, Jagdish
<x xml:space="preserve">Abstract</x> Crouzon syndrome is a rare genetic disorder. It is inherited as an autosomal dominant pattern. Mutations in the FGFR2 gene are known to cause Crouzon syndrome. Craniofacial abnormalities are common at birth and may progress with time. The severity of these signs and symptoms varies among affected children. A full term, large for date, male baby was delivered to a gravida 2 mother by cesarean section having facial dimorphism suggestive of Crouzon syndrome. Genetic team confirmed the diagnosis. Baby had severe respiratory distress. On work up, upper bony airway narrowing was found (diameter 3 mm). Later on, baby was operated for the same. Baby is asymptomatic now and doing well up to 2 months of follow-up. Management of Crouzon disease is multidisciplinary and early diagnosis has prime importance. Follow-up must ensure late features like hearing problems, vision problems, dental problems, intelligence, cranial synostosis, and upper airway problems.